2022
DOI: 10.3390/pathogens11111328
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative G6PD Deficiency Screening in Routine Malaria Diagnostic Units in the Brazilian Amazon (SAFEPRIM): An Operational Mixed-Methods Study

Abstract: Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency testing is not routinely performed before primaquine treatment in most Plasmodium vivax endemic areas, despite the risk of primaquine-associated hemolysis. This is due to the operational challenges associated with pragmatic G6PD testing and as such needs to be addressed. Methods and findings: This mixed-methods operational study was aimed at implementing the quantitative point-of-care StandardTM G6PD (SD Biosensor, Korea) screening test in malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“… 45 Some barriers to its implementation in remote and low-resourced locations remain, including a need for training and a high cost for the devices and test strips. 46 …”
Section: Discussionmentioning
confidence: 99%
“… 45 Some barriers to its implementation in remote and low-resourced locations remain, including a need for training and a high cost for the devices and test strips. 46 …”
Section: Discussionmentioning
confidence: 99%
“…However, the authors found limitations linked to technical and cultural aspects that should be addressed when expanding screening to larger areas (37).…”
Section: Discussionmentioning
confidence: 99%
“…A study on barriers and facilitators for G6PD test implementation (36) identified three main barriers: perceived low risk of hemolysis, wrong perception of P. vivax malaria as a benign condition, and the cost of routine testing as part of the healthcare attention of malaria patients. A study conducted in Brazil on the operational challenges associated with pragmatic G6PD testing (37) found that the StandG6PD-BS PoC test was well accepted by both healthcare professionals and patients and can be performed at malaria treatment units in the Brazilian Amazon to inform treatment decisions with PQ. However, the authors found limitations linked to technical and cultural aspects that should be addressed when expanding screening to larger areas (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an operational study in Brazil implementing the STANDARD G6PD, the study location with the lowest case load had the lowest assessment score at 6 months after initial training. As such, the authors suggest refresher training every 6 months in such locations [ 146 ].…”
Section: Early Experiences With the Implementation Of Poc G6pd Testingmentioning
confidence: 99%